Harnessing the potential of 2D Material-Conducting polymer composite aerogels for energy and environmental applications - Ansari, Usama; Kashyap, Shivam; Singh, Ankita; Maken, Sanjeev; Poddar, Deepak; Thakur, Sanjeeve (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
[Display omitted] •3D inorganic-polymer composite aerogel for energy and environmental application.•Physical and Chemical crosslinking mechanisms in composite aerogels.•Study of various parameters that affects the properties of composite aerogels.•Fabrication processes of composite aerogels and superiority over each other.•Challenges and future scope involved in the fabrication processes of 2DCP aerogels. The 3D aerogel structured two-dimensional (2D) materials such as graphene and transition metal chalcogenides have received considerable attention in the arena of advanced materials due to their distinctive features such as hexagonal planar structure, high surface area, exceptional mechanical strength, electrical conductivity, and optical transparency. These properties make them ideal candidates for various applications including energy storage, hydrogen evolution reaction (HER), gas sensing and adsorption, water remediation, and more. This paper offers a thorough examination of 2D materials conducting polymer (2DCP) composite aerogels, covering different production methods, interactions, and applications. The paper discusses fabrication methods for composite aerogels, highlighting the significance of exact morphology, controlled mechanical strength, porosity, and architecture to obtain desired properties. The versatility of these composites is demonstrated in varied disciplines such as electrodes in supercapacitors, lithium-ion batteries, and fuel cells in energy storage and conversion applications because of their superior specific surface area, outstanding electrical conductivity, and chemical stability. Additionally, their adaptability in solving environmental and energy-related concerns is comprehensively examined, particularly in gas sensing applications, water remediation, HER, and gas adsorption. The study investigates the fundamental principles responsible for the exceptional qualities and performance of these composite materials, offering valuable insights for further optimisation and design. The article highlights the existing challenges and future prospects in this growing subject, highlighting the necessity for ongoing research to fully exploit the promise of 2DCP aerogel composites for many practical uses.